A detailed model of direct dry-cooling for the supercritical carbon dioxide Brayton power cycle. (25th December 2019) - Lock, Andrew; Hooman, Kamel; Guan, Zhiqiang
Highlights: Detailed model developed for sCO2 -air finned tube heat exchangers. Heat exchanger area sized for dry-cooled sCO2 Recompression cycle. The sCO2 heat transfer correlation selected has a significant effect on results. Forced convection and natural draft cooling towers perform comparably at off-design ambient temperatures. Internal buoyancy effects may occur in sCO2 finned tubes. Abstract: This study describes a detailed numerical model of large diameter finned tube heat exchangers for a dry-cooled supercritical carbon dioxide (sCO2 ) Brayton cycle. Multiple-row heat exchangers are discretised into two-dimensional cells, and physical properties and heat transfer coefficients are evaluated locally at each cell to account for the large changes in sCO2 properties near the critical point. Air-flow is modelled as either forced draft, or natural draft within a natural draft dry cooling tower (NDDCT) model. Conditions anticipated for sCO2 Recompression cycle heat rejection are used to determine the heat exchanger area required for the cycle. The influence of different correlations for sCO2 -side heat transfer is studied, showing that up to 27% more heat exchange area is predicted using generic-fluid heat transfer correlations when compared to those developed specifically for sCO2 . The model is used to determine the effect of design ambient temperature on the heat exchanger size, as well as heat exchanger performance at elevated off-design ambient temperatures. Criteria for the presence of buoyancy effects in sCO2 flow from literature are shown to be exceeded by an order of magnitude under the conditions modelled, demonstrating that uncertainty remains regarding of the behaviour of sCO2 heat transfer under these conditions.